(untitled) (Research, Society and Development, 2020)
The estimated global prevalence of patients on chronic dialysis has progressively increased in Brazil. The life of an individual with chronic renal failure goes through a variety of losses from the moment the disease is diagnosed, which can sometimes lead to lack of adherence to treatment. Therefore, the study aims to know the factors that influence adherence to the treatment of patients with chronic non-transmissible damage, especially those who have chronic renal failure undergoing hemodialysis. An integrative review was carried out, consisting of eight articles selected from the Lilacs and Scielo databases between 2005 and 2020. The studies pointed out the following categories: Support from the family as support for adherence; Factors related to the nature of therapy and information for the construction of knowledge. With the survey of the main factors, it was possible to increase the knowledge on the subject, in order to encourage both the patient and the health professional, who is a mediator of this cause so significant to promote the well-being and relief of suffering that affects the hemodialysis patient. Nursing care must be based on a reciprocal relationship, in which information is exchanged, in a partnership between the patient, health teams, family and community to optimize the patients’ quality of life.